Associa????es entre humor, sinais cl??nicos, desempenho funcional e a fun????o auton??mica em pacientes com Doen??a de Parkinson e o efeito de um programa de caminhada na variabilidade da frequ??ncia card??aca e no desempenho funcional - Rodrigues, Fabio Barreto (2015)
The reduced dopamine production in Parkinson's disease (PD) substantially affects the motor skills and other primary bodily functions, including mood, cognition and functional performance. At the same time, losses occur in the autonomic nervous system. It is unknown how the autonomic function is related to these losses and whether a walking program can modify the heart rate variability (HRV) in this population. The aim of this study was to assess HRV in patients with PD and its relationship with anxiety and depression symptons, functional performance and severity of disease, and also the effect of a walking program in autonomic modulation and functional capacity. In cross- sectional phase were evaluated 26 patients (16 men / 10 women, 57.4 ?? 9.2 years) using the scales of anxiety, depression (HADS-A and HADS-D) and disease severity (UPDRS motorexamination and Hoehn and Yahrd scales). Functional performance was evaluated by the Timed Up and Go test (TUG) and three tests from the Senior Fitness Tests. These results were correlated with HRV indexes of time (RMSSD, SDNN) and frequency domain (HF, LF, LF / HF, TP, HF / TP, LF / TP) and nonlinear analysis (SampEn and DFA1) measured in sitting and standing position. The HRV variation from sitting to standing position (??? analysis) was also considered. In longitudinal phase a walking group (WG, n = 13) and a control group (CG n = 6) were formed through a randomized controlled trial. The home-based walking program had a duration of six weeks. The patients in the WG group were reassessed after 12 weeks of training. Were observed high levels of anxiety (30.7%) and depression (34.6%) in the patients evaluated. Depressive symptoms were associated to the parasympathetic activity: RMSSD (r = - 0.382; p ??? 0.05), as the activity in the both sympathetic and parasympathetic branches: LFseated (r = -0383; p ??? 0.05), LFstanding (r = -0.411; p ??? 0.05), TPstanding (r = -0, 504, p ??? 0.05) and ??? SampEn (r = -0384, p ??? 0.05). The severity and duration of illness also were negatively associated with autonomic function. RMSSDseated (r = -0.438; p ??? 0.05), SDNNseated (r = -0.452; p ??? 0.05) SDNNstanding (r = -0.602, p ??? 0.01); LFstanding (r = -0.603; p ??? 0.01); TPstanding (r = -0.504; p ??? 0.05) and LF/ TPstanding (r = -0.504; p ??? 0.05) were negatively associated with time to perform the TUG test. Other significant correlations (p ??? 0.05) of physical and functional tests and age HRV were observed . The six-weeks walking program have promoted significant changes in SampEn index (which measures the irregularity of HR data) in WG group compared to the CG group (20.47 vs -22.81%; CA and CO, respectively; p = 0.033) as well as ???SampEn measure (-22.83% vs. 18.46; WG and CG, respectively; p = 0.022), suggesting positive changes in autonomic function. At week 12, the WG group patients exhibited increased ratios of HF/TPstanding (7.0%; p = 0.017) and SampEn-standing (20.5%; p = 0.008; respectively), and reduction of the LF/HFstanding index (-10.65%; p = 0.012 ) compared to the first week, suggesting improvements in autonomic balance. There was an increase in sit-to-stand repetitions (10.50 ?? 1.93 to 13.25 ?? 1.58 repetitions; p = 0.021) and reduced time to perform the TUG test (7.34"?? 0.67 to 6.91" ?? 0.83, p = 0.002). Several HRV indices measured before walking program (SDNN, RMSSD, LF, HF, LF / TP) have shown correlations with the functional gain (r2 ranging from 0.62 to 0.81), suggesting a role of autonomic function in neuromuscular adaptation to training. It follows that HRV may work as an integrative measure and also as a peripheral marker of body's adaptability and its self-regulatory capacity, besides a practical and sensitive tool e to the disease progression. The home-based walking program have improved autonomic function of participants, often hampered by the disease. This is particularly interesting in that many bodily functions impaired in PD are mediated by autonomic function.